About stability of delay differential equations with square integrable level of stochastic perturbations. (April 2019) - Shaikhet, Leonid
Abstract: The long term behavior of solutions of stochastic delay differential equations with a fading stochastic perturbations is investigated. It is shown that if the level of stochastic perturbations fades on the infinity, for instance, if it is given by square integrable function, then an asymptotically stable deterministic system remains to be an asymptotically stable (in mean square).